A state-of-the-art review on spent coffee ground (SCG) pyrolysis for future biorefinery. (January 2022) - Atabani, A.E.; Ali, Imtiaz; Naqvi, Salman Raza; Badruddin, Irfan Anjum; Aslam, Muhammad; Mahmoud, Eyas; Almomani, Fares; Juchelková, Dagmar; Atelge, M.R.; Khan, T.M. Yunus
Abstract: Coffee is a globally consumed beverage that produces a substantial amount of valuable organic waste known as spent coffee grounds (SCG). Although SCG is a non-edible biomass, research initiatives focused on valorizing/utilizing its organic content, protecting the environment, and reducing the high oxygen demand required for its natural degradation. The integration with biorefinery in general and with pyrolysis process in specific is considerered the most successful solid waste management strategy of SCG that produce energy and high-value products. This paper aims at providing a quantitative analysis and discussion of research work done over the last 20 years on SCG as a feedstock in the circular bioeconomy (CBE). Management stratigies of SCG have been thoroughly reviewed and pyrolysis process has been explored as a novel technology in CBE. Results revealed that explored articles belong to Chemical, physical., biological and environmental science branches, with Energy & Fuels as the most reporting themes. Published works correlate SCG to renewable energy, biofuel, and bio-oil, with pyrolysis as a potential valorization approach. Literature review showed that only one study focused on the pyrolysis of defatted spent coffee grounds (DSCG). The insightful conclusions of this paper could assist in proposing several paths to more economically valorization of SCG through biorefinery, where extracted oil can be converted to biofuels or value-added goods. It was highlighted the importance of focusing on the coupling of SCG with CBE as solid waste managment strategy. Highlights: Spent coffee ground is a promising organic waste for biochar & bio-oil production. Fast pyrolysis is the best technique to obtain optimum yield of bio-oil. The maximum bio-oil yield has been reported at 500 °C. Bio-oil contains a considerable amount of hydrocarbons and phenol. Therefore, it can be used either as a fuel or pesticide.